Detection of melamine by using carboxyl-functionalized Ag-COF as a novel SERS substrate. (1st February 2023) - Yang, Zichen; Ma, Chaoqun; Gu, Jiao; Wu, Yamin; Zhu, Chun; Li, Lei; Gao, Hui; Yin, Wenzhi; Wang, Zirui; Chen, Guoqing
Highlights: The novel Ag-COF-COOH substrates provide huge SERS hot spots, EF = 9.72 × 10 6 . The SERS method in this work is sensitive and the LOD is 0.68 μg/L in milk. The SERS method in this work requires only one step of pretreatment. Abstract: Melamine, a nitrogen-containing organic molecule, has received widespread attention as it had been illegally added in dairy products to increase the content of nitrogen, leading to kidney stones in healthy people after long-term ingestion. Based on SERS technology and Covalent Organic Framework (COF) materials, we developed carboxyl-functionalized Ag-COF-COOH materials as SERS substrates for the detection of melamine adulteration. Using COF material as a ligand can effectively reduce the influence of interferents in milk. In addition, we investigated two causes of melamine SERS enhancement: the ordered arrangement of Ag NPs and the strong interaction between the substrate and the melamine. The linear range was 1–20 μg/L and the limit of detection (LOD) was 0.68 μg/L in liquid milk due to the high sensitivity and reliability of this method. The results show that this new SERS substrate has great potential for applications in the food surveillance industry.